2012
DOI: 10.2741/522
|View full text |Cite
|
Sign up to set email alerts
|

TGF-beta 1/Smad3 expression and its effects on carotid intimal hyperplasia

Abstract: We investigated expression of TGF-beta 1/Smad3 after balloon injury in rat carotid arteries as well as the effects of blocking the TGF-beta 1/smad3 signaling pathway on carotid intimal hyperplasia. Rats were randomly divided into control group (C group) and injury group (S group). The latter were randomly divided into intervention group (antisense Smad3 adenovirus vector transfection after balloon injury) and blank control group (blank adenovirus vector transfection after balloon injury). Expression of Smad3 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…26 We (and others) have also demonstrated in vivo that following gene transfer of Smad3, TGF- β enhances SMC proliferation as well as IH, whereas reducing Smad3 inhibits IH. 2, 34, 35 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 We (and others) have also demonstrated in vivo that following gene transfer of Smad3, TGF- β enhances SMC proliferation as well as IH, whereas reducing Smad3 inhibits IH. 2, 34, 35 …”
Section: Discussionmentioning
confidence: 99%
“…We and others have already demonstrated that Smad3 has an independent stimulatory effect on IH. 2, 34 …”
Section: Discussionmentioning
confidence: 99%
“…TGF-β1/Smad2/3 signaling is a critical regulator in the pathological process of intimal hyperplasia and inhibition of the TGF-β1/Smad2/3 signaling pathway may reduce VSMC proliferation and collagen deposition, thus attenuating intimal hyperplasia ( 15 17 ). Therefore, the present study investigated whether the reduced VSMC proliferation and collagen deposition were mediated via TGF-β1/Smad2/3 pathway.…”
Section: Resultsmentioning
confidence: 99%
“…TGF-β1/Smad2/3 signaling has a key role in intimal hyperplasia; therefore, inhibition of the TGF-β/Smad2/3 signaling pathway may reduce VSMCs proliferation and collagen deposition, thus attenuating intimal hyperplasia ( 15 17 ). It is of note that the present study determined that honokiol treatment downregulated the protein expression level of p-Smad2/3, whereas the level of TGF-β1 and total Smad2/3 remained constant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation